Growth Orchid (♀) Dendrobium Liniale x (♂) Dendrobium Biggibum on Medium NAA and Organic Material in Vitro - Sri Hartati; Heni Purwanti; Nandariyah Nandariyah (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2021)
The research aimed to study the influence of the application of NAA concentration, the addition of organic materials and a combination of both on media Knudson C towards the growth of orchid plantlet (♀) Dendrobium liniale >< (♂) Dendrobium biggibum. The purpose of using media Knudson C in culture in vitro is to optimize the growth of orchid plantlet Dendrobium liniale and Dendrobium biggibum. The experiments were carried out in the Laboratory of Plant Physiology and Biotechnology Faculty of Agriculture, Sebelas Maret University Surakarta. The research used Complete Randomized Design (CRD) with 2 treatment factors, factor I was the concentration of NAA (0 ppm, 1 ppm, 3 ppm and 5 ppm); and factor II was the organic materials (coconut water, banana, potatoes and sweet potatoes). In total there were 20 treatment combinations . Each combination was repeated four times. The results showed that the combination of sweet potato and NAA 5 ppm produced the following characteristics: the fastest root growth, most root length, and the largest number of leaves; while the combination of banana extracts and NAA 5 ppm produced a number of roots, the shoots appear most rapidly, and the highest number of shootsKeywords: genetic diversity; tissue culture; medium;